Ethical issues in access to and delivery of emergency department care in an era of changing reimbursement and novel payment models - Chadd K. Kraus; John C. Moskop; Kenneth D. Marshall; Kelly Bookman; ACEP Ethics Committee (Journal of the American College of Emergency Physicians Open)
Abstract Hospital emergency departments (EDs) and the emergency physicians, nurses, and other health professionals who provide emergency care in them, are a critical component of the United States (US) health care system in the 21st century. Although access to emergency care has become a de facto right in the United States, funding for emergency care is fragmented and complex, which causes confusion and conflict about who should bear the cost of care. This article examines the tension between universal access to emergency care in the United States and the fragmentary, tenuous, and contentious financial arrangements that make it possible, viewing the issue in context of the historical development, legal and moral foundations, current situation, and future challenges of ED care in the United States. It begins with a review of the origins and evolution of emergency care and of hospital EDs in the United States. It then examines arguments for a right to emergency medical care and for shared obligations of patients to seek and of professionals and society to provide that care. Finally, it reviews current strategies and future prospects for protecting access to emergency care for patients who require it.